2018
DOI: 10.3390/polym10040409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 Content on the Extended Creep Behavior of SiO2-Based Wood-Inorganic Composites Derived via the Sol–Gel Process Using the Stepped Isostress Method

Abstract: In this study, methyltrimethoxysilane (MTMOS) was used as a reagent to prepare SiO 2 -based wood-inorganic composites (WIC SiO 2 ) via the sol-gel process, and subsequently, the extended creep behaviors of WIC SiO 2 with weight percent gains (WPGs) of 10%, 20%, and 30% were estimated using the stepped isostress method (SSM). The results revealed that the density of all samples ranged from 426 to 513 kg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…All SSM tests were performed at 20 °C, which is below the glass transition temperature ( T g ), thus, the Eyring model (Equation (2)) is used to calculate the activation volume in this study [29]. This model was applied to estimate the shift factor (α σ ), which shows the following express rate with the stress level [25,28]:logασ=log(sans-serifε˙sans-serifε˙r)=V*2.303kT(sans-serifσσref) where sans-serifε˙ and sans-serifε˙r are respectively the creep rate at the elevated stress (σ) and reference stress (σ ref ), V * is the activation volume, k is Boltzmann’s constant (1.38 × 10 −23 J/K), and T is the absolute temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All SSM tests were performed at 20 °C, which is below the glass transition temperature ( T g ), thus, the Eyring model (Equation (2)) is used to calculate the activation volume in this study [29]. This model was applied to estimate the shift factor (α σ ), which shows the following express rate with the stress level [25,28]:logασ=log(sans-serifε˙sans-serifε˙r)=V*2.303kT(sans-serifσσref) where sans-serifε˙ and sans-serifε˙r are respectively the creep rate at the elevated stress (σ) and reference stress (σ ref ), V * is the activation volume, k is Boltzmann’s constant (1.38 × 10 −23 J/K), and T is the absolute temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In the past few years, the stepped isostress method (SSM), which can evaluate the creep behavior of a single sample by a stepped increase of the stress level [24,25,26,27], was shown to be more beneficial in assessing the creep behavior of low-thermal-conductivity materials (e.g., wood and wood composites) compared to the SIM [28]. A previous study demonstrated that wood treated with methyltrimethoxysilane (MTMOS) could effectively enhance its creep resistance [29]. However, to the best of our knowledge, the effect of different metal alkoxides on the creep behavior of WICs has not been studied using the SSM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, wood with a microporous structure can combine a natural porosity scaffold with inorganic/organic compounds. Therefore, many efforts have been devoted to creating functionalized wood by dispersing inorganic and organic components into the wood matrix in order to endow these wood-based materials with new properties, such as biodegradation resistance [2], rheological properties [3], mechanical properties [4,5,6], acoustic properties [7], and magnetic properties [8]. Among these properties, magnetism has recently received much attention.…”
Section: Introductionmentioning
confidence: 99%